Identification and Characterization of Nep1-Like Proteins From the Grapevine Downy Mildew Pathogen Plasmopara viticola - Schumacher, Stefan; Grosser, Katrin; Voegele, Ralf Thomas; Kassemeyer, Hanns-Heinz; Fuchs, René (Frontiers in Plant Science, 2020)
The obligate biotrophic oomycete Plasmopara viticola causes tremendous problems in viticulture by evoking grapevine downy mildew. P. viticola, like other plant pathogens, achieves infection by suppression of plant innate immunity by secretion of effector molecules into its host plant. An ever-expanding family of proteins with effector-like characteristics is formed by the “Necrosis and Ethylene inducing peptide 1 (Nep1) – like proteins” (NLPs). NLPs can be divided into two groups by their ability to induce necrosis. While cytotoxic NLPs may act as virulence factors for a necrotrophic or hemibiotrophic plant pathogen, the role of non-cytotoxic NLPs is so far unknown. In this study we identified eight independent NLPs in P. viticola and selected three for functional analysis. While one was identified as a putative pseudo gene, two contain all so far described critical key elements for necrosis formation except for an N-terminal signal peptide. Further characterization revealed that none of the putative necrosis elicitors was able to actually induce necrosis, neither in several susceptible or resistant Vitis species nor in the dicot model plant Nicotiana benthamiana. This inability exists independently of the presence or absence of a signal peptide. However, any possible mechanism for the suppression of the ability to induce necrosis in planta was not detected. Interestingly, expression analysis of the presumed pseudo gene revealed remarkable differences between pure sporangia solution and sporangia in the presence of leaf material. To our knowledge, this is the first report of this kind of regulation that suggests an important function of so far nonfunctional “pseudo” NLP genes during the first hours of infection.